Implementing result based budget management frameworks an assessment of progress in selected countries. (Asian Development Bank, 2017)
The use of results based budget management (RBBM) is well established around the world as a concept. RBBM is intended to hold managers to account for their role in organizing the supply of goods and services to the public, and to enforce a regular review of the effectiveness of government expenditure programs. However, there would appear to be significant gaps between concept and implementation. In order for governments to gauge policy effectiveness, a statistical framework must be developed to define outputs and outcome indicators. This publication examines a select group of countries that have led the use of RBMM. It also identifies weaknesses in their implementation from a statistical analysis perspective and suggests guidelines for the development of output descriptions, output indicators, and outcome indicators.